Talking Cure Models: A Framework of Analysis - Marx, Christopher; Benecke, Cord; Gumz, Antje (Frontiers in Psychology, 2017)
Psychotherapy is commonly described as a “talking cure,” a treatment method that operates through linguistic action and interaction. The operative specifics of therapeutic language use, however, are insufficiently understood, mainly due to a multitude of disparate approaches that advance different notions of what “talking” means and what “cure” implies in the respective context. Accordingly, a clarification of the basic theoretical structure of “talking cure models,” i.e., models that describe therapeutic processes with a focus on language use, is a desideratum of language-oriented psychotherapy research. Against this background the present paper suggests a theoretical framework of analysis which distinguishes four basic components of “talking cure models”: (1) a foundational theory (which suggests how linguistic activity can affect and transform human experience), (2) an experiential problem state (which defines the problem or pathology of the patient), (3) a curative linguistic activity (which defines linguistic activities that are supposed to effectuate a curative transformation of the experiential problem state), and (4) a change mechanism (which defines the processes and effects involved in such transformations). The purpose of the framework is to establish a terminological foundation that allows for systematically reconstructing basic properties and operative mechanisms of “talking cure models.” To demonstrate the applicability and utility of the framework, five distinct “talking cure models” which spell out the details of curative “talking” processes in terms of (1) catharsis, (2) symbolization, (3) narrative, (4) metaphor, and (5) neurocognitive inhibition are introduced and discussed in terms of the framework components. In summary, we hope that our framework will prove useful for the objective of clarifying the theoretical underpinnings of language-oriented psychotherapy research and help to establish a more comprehensive understanding of how curative language use contributes to the process of ther-apeutic change.